Variation in hunting behaviour in neighbouring chimpanzee communities in the Budongo forest, Uganda. - Catherine Hobaiter; Liran Samuni; Caroline Mullins; Walter John Akankwasa; Klaus Zuberbühler (PLoS ONE, 2017)
Hunting and sharing of meat is seen across all chimpanzee sites, with variation in prey preferences, hunting techniques, frequencies, and success rates. Here, we compared hunting and meat-eating behaviour in two adjacent chimpanzee communities (Pan troglodytes schweinfurthii) of Budongo Forest, Uganda: the Waibira and Sonso communities. We observed consistent between-group differences in prey-species preferences and in post-hunting behaviour. Sonso chimpanzees show a strong prey preference for Guereza colobus monkeys (Colobus guereza occidentalis; 74.9% hunts), and hunt regularly (1-2 times a month) but with large year-to-year and month-to-month variation. Waibira chimpanzee prey preferences are distributed across primate and duiker species, and resemble those described in an early study of Sonso hunting. Waibira chimpanzees (which include ex-Sonso immigrants) have been observed to feed on red duiker (Cephalophus natalensis; 25%, 9/36 hunts), a species Sonso has never been recorded to feed on (18 years data, 27 years observations), despite no apparent differences in prey distribution; and show less rank-related harassment of meat possessors. We discuss the two most likely and probably interrelated explanations for the observed intergroup variation in chimpanzee hunting behaviour, that is, long-term disruption of complex group-level behaviour due to human presence and possible socially transmitted differences in prey preferences.